An Assessment of Factors Affecting Marketing Performance of Firms Led by Female Executives - .A PhD, Ayogyam; .L, Asare-Kyire; .E, Boateng; F, Amo.; .A PhD, Amoako (British Journal of Marketing Studies, 2013)
The purpose of this research is to identify and assess factors that affect marketing performance in firms whose management team are being led by women. This has become important because previous writers have expressed mixed feelings about the performance of such firms. The units for the research were 148 female executives/managers from some firms in the country. In selecting respondents for this study, the purposive sampling procedure was adopted since only women managers were being targeted. Based on the body of literature developed and the field work assessment, some hypotheses were proposed which were later on tested using the Pearson Chi-squared test. For the sake of this study, marketing performance was restricted to; the ability the make good sales, the ability to retain customers and the ability to maintain discipline in the firm. The above performance indicators were measured against some identified characteristics and issues concerning women. Issues such as; age of a woman, marital status of a woman, character of a woman, means of progression to top position within the firm and mode of remuneration for women leaders. Some of the findings of this study include the fact that; Ghanaian women affect sales performance if they are extrovert in character, above the age of forty (40), married, appointed into positions in the firm from outside the organization and remunerated on commission basis. Again, the ability to maintain discipline in a firm has no association with the mode of remuneration and the marital status of the woman